Egf binding to its receptor triggers a rapid tyrosine phosphorylation of the erbB-2 protein in the mammary tumor cell line SK-BR-3. - King, C R (1988)
The epidermal growth factor receptor (EGF-R) and the erbB-2 proto-oncogene product protein are closely related by their structural homology and their shared enzymatic activity as autophosphorylating tyrosine kinases. We show that in mammary tumor cells (SK-BR-3) EGF causes a rapid increase in tyrosine phosphorylation of the erbB-2 protein. Phosphorylation of erbB-2 does not occur in cells lacking the EGF-R (MDA-MB-453). Phosphorylation of erbB-2 in SK-BR-3 cells is blocked if EGF is prevented from interacting with its receptor by specific monoclonal antibodies. While EGF induces the down-regulation of its receptor in SK-BR-3 cells, EGF has no effect on the stability of the erbB-2 protein. This result suggests that the erbB-2 protein is a substrate of the EGF-R and indicates the possibility of communication between these two proteins early in the signal transduction process.